Trinny & Susannah What Your Clothes Say About You : How to Look Different, Act Different and Feel Different - Woodall, Trinny and Constantine, Susannah (London Weidenfeld & Nicolson, 2005)
What do your clothes say about you? Trinny and Susannah show how you can change your image through how you dress and thereby improve confidence and self-esteem. The book will accompany an 11-part BBC1 television series.
Include Illustration
Keywords: Beauty, Personal -- Clothing and dress--Psychological aspects -- Self-actualization (Psychology)